2021
DOI: 10.20944/preprints202106.0345.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effects of Temperature and Salinity Stressors on the Survival, Condition, and Valve Closure of the Manila Clam, Venerupis philippinarum in a Holding Facility

Abstract: We investigated the response of the Manila clam Venerupis philippinarum to possible temperature and salinity changes in a holding facility. First, clams were exposed to four temperatures for 15 days. Valve closure and survival of clams exposed to seawater at 18℃ were higher than that of those exposed to seawater at 24℃. Second, clams were exposed to six salinities for 15 days. Survival of clams exposed to two salinity fluctuation conditions (24–30 and 27–24 psu) was lower than that of clams… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(42 reference statements)
1
0
0
Order By: Relevance
“…High temperature at noon in summer, in conjunction with low water levels on the grow‐out ground (during low tide, or in puddles on the grow‐out ground), has an extreme effect on cultured clams, seeming to ‘boil’ them (Figure 6a). These findings align with previous studies in which temperatures outside the bivalve's optimal range can affect their respiration, metabolic activity, feeding, ingestion rates, growth and survival (Bae et al, 2021; Han et al, 2008; Hornstein et al, 2018; Xiao et al, 2014). Research also demonstrated that temperatures beyond the species' optimal range influence the bivalve's immune system, leading to a less effective response to infectious disease agents (Matozzo et al, 2012; Nardi et al, 2021; Rahman et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…High temperature at noon in summer, in conjunction with low water levels on the grow‐out ground (during low tide, or in puddles on the grow‐out ground), has an extreme effect on cultured clams, seeming to ‘boil’ them (Figure 6a). These findings align with previous studies in which temperatures outside the bivalve's optimal range can affect their respiration, metabolic activity, feeding, ingestion rates, growth and survival (Bae et al, 2021; Han et al, 2008; Hornstein et al, 2018; Xiao et al, 2014). Research also demonstrated that temperatures beyond the species' optimal range influence the bivalve's immune system, leading to a less effective response to infectious disease agents (Matozzo et al, 2012; Nardi et al, 2021; Rahman et al, 2018).…”
Section: Discussionsupporting
confidence: 91%